Sirtuins and Gut Microbiota: Dynamics in Health and a Journey from Metabolic Dysfunction to Hepatocellular Carcinoma - Mahmoud Zhra; Muhammad Affan Elahi; Aamira Tariq; Ahmed Abu-Zaid; Ahmed Yaqinuddin (Cells)
Metabolic dysfunction leading to non-alcoholic fatty liver disease (NAFLD) exhibits distinct molecular and immune signatures that are influenced by factors like gut microbiota. The gut microbiome interacts with the liver via a bidirectional relationship with the gut–liver axis. Microbial metabolites, sirtuins, and immune responses are pivotal in different metabolic diseases. This extensive review explores the complex and multifaceted interrelationship between sirtuins and gut microbiota, highlighting their importance in health and disease, particularly metabolic dysfunction and hepatocellular carcinoma (HCC). Sirtuins (SIRTs), classified as a group of NAD+-dependent deacetylases, serve as crucial modulators of a wide spectrum of cellular functions, including metabolic pathways, the inflammatory response, and the process of senescence. Their subcellular localization and diverse functions link them to various health conditions, including NAFLD and cancer. Concurrently, the gut microbiota, comprising diverse microorganisms, significantly influences host metabolism and immune responses. Recent findings indicate that sirtuins modulate gut microbiota composition and function, while the microbiota can affect sirtuin activity. This bidirectional relationship is particularly relevant in metabolic disorders, where dysbiosis contributes to disease progression. The review highlights recent findings on the roles of specific sirtuins in maintaining gut health and their implications in metabolic dysfunction and HCC development. Understanding these interactions offers potential therapeutic avenues for managing diseases linked to metabolic dysregulation and liver pathology.